Earwitnessing the Queer Acoustics of Public Space: Law, Sex and Nature in Ultra-red’s Second Nature - David C Jackson (Law Text Culture, 2020)
This paper examines queer sex and public space usage in Los Angeles’ Griffith Park through a series of recordings produced by the sound collective Ultra-red. Ultra-red have been using sound as a mode of political analysis since 1994 when they were founded by two AIDS activists in Los Angeles. This paper works in particular with two records released by Ultra-red in the late 1990s: an EP Ode to Johnny Rio (1998) and album Second Nature: An Electroacoustic Pastoral (1999), which are often referred to collectively as the Second Nature. For the Second Nature project, they draw their sound material from the public and private soundscapes of everyday queer life and cruising in Griffith Park. Ultra-red’s compositions rely on looping, fragmentation, and a radical approach to cutting audio. This disrupts both the musicality and linearity we might expect from recordings that present themselves almost as documentaries that pits queer behaviors, bodies, and identities against the suburban conceits of those who call for laws that curb the behavior in the park through policing, entrapment, barring traffic, and issuing tickets to gay men for loitering and sexual behavior.